Multimorbidity as a Risk Factor of Elder Abuse/Mistreatment in India: A Cross-Sectional Study - Sathya, T (Journal of interpersonal violence, 2022)
Globally, elder abuse/mistreatment is a common form of violence against the elderly. This study examines the association between multimorbidity and abuse/mistreatment among the elderly population (60+) in India. Cross-sectional data from the United Nations Population Fund (UNFPA)?s ?Building Knowledge Base on Population Aging in India? (BKPAI, 2011) was analyzed. We generated a multimorbidity variable by combining 20 self-reported diagnosed chronic diseases. Bivariate analysis was used to understand the sample distribution and prevalence estimation of elder abuse/mistreatment by multimorbidity and state. Furthermore, multilevel mixed-effect logistic regression was used to examine the association between multimorbidity and elder abuse/mistreatment. The overall prevalence of elder abuse/mistreatment in the study population is 11.4%. The prevalence of elder abuse/mistreatment among elderly with no chronic diseases is 6.01% which increases to 22.7% among elderly with four or more chronic diseases. Furthermore, the result from the multilevel mixed-effect logistic regression showed a close association between multimorbidity and elder abuse. Elderly with two, three, and four or more chronic diseases are 3.02 (CI = 2.33, 3.91, p < .000), 4.16 (CI = 3.02, 5.74, p < .000), and 5.06 (CI = 3.50, 7.31, p <.000) times more likely to experience abuse/mistreatment than elderly with no chronic diseases, respectively. In specific, this association is stronger for the elderly population residing in the urban areas. Furthermore, economic status and educational attainment have a protective role in determining elder abuse/mistreatment in India. In conclusion, multimorbidity has emerged as a significant risk factor of elder abuse/mistreatment in India. Measures to prevent elder abuse should consider the role of multimorbidity.